HAM DALAM RUANG DOMESTIK Studi terhadap UU. No. 23 Tahun 2004 Tentang PKDRT - Shulton Asnawi, Habib (Islamic University of Indonesia, 2010)
This article describes about Domestic Violence: Perspectives of the Act. No. 23 of 2004 on Domestic Violence: An Effort In the Struggle for Human Rights